WANITA HAMIL DAN MENYUSUI YANG MENINGGALKAN PUASA RAMADHAN DALAM PERSPEKTIF HANAFIYAH DAN SYAFI'IYAH - Amri Effendi (Institut Agama Islam Negeri Batusangkar, 2019)
Fasting is one of the pillars of Islam that must be shown by someone who has fulfilled certain requirements. Islamic scholars agree that the fasting of Ramadan must be carried out by every adult, resourceful, Muqim (in his place of residence), and healthy as long as he/she has not been a barrier to fasting, such as menstruation and Nifas for women. The purpose of this discussion is to explain the perspective of Hanafiyah and Shafi'yah against pregnant and nursing women who avoided the fasting of Ramadan. This type of research is a library research (literature research). The results shows that the perspective of Hanafiyah Ulama and Syafi'iyah Ulama about the consequences of the law on pregnant and nursing women who avoided the Ramadan fasting due to fear of safety of herself and her son there are differences of opinion. There were distinction opinion in establishing mandatory fidyah as a result of its law while in concerning fasts agreed upon by both.